GCCA+ Climate Smart Agriculture and Advisory Services Tools Training of Trainers and Validation of Climate Smart Agriculture Handbook - Magagula, Futhi (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
In Sub-Sahara Africa agriculture is predominantly rainfed and faces several challenges due to unpredictable weather patterns and distribution that is amplified by climate change. The rising temperatures, changes in precipitation patterns, and increased frequency of extreme events contribute to the vulnerability of farmers as well as leading to crop failure, low yields, land degradation among others. These factors compound the difficulties for smallholder farmers, making it more challenging for them to produce adequate food to meet the demands of a growing population. Many Sub-Sahara African governments, as well as international organizations, have dedicated significant resources to advance Climate-smart agriculture (CSA) as a strategy to enhance resilience against the adverse impacts of climate change in developing countries. CSA is a combination of several sustainable farming practices that target addressing the challenges posed by climate change and variability. Hence, it is an approach focused on identifying and aligning agricultural systems and supportive institutions that are well-suited to address the location or site-specific challenges posed by climate change. This underscores the idea that there is no universally recommended "one size fits all" CSA practice, highlighting the importance of understanding the context and placing emphasis on adaptation as crucial factors for promoting widespread adoption. Some of the CSA practices include agroforestry, conservation agriculture, water harvesting, integrated soil fertility management, crop diversification, water management, and improved seeds, among others. As it addresses the challenges caused by climate change, CSA also promotes agricultural productivity, environmental sustainability, and food security. Therefore, CSA involves the integration of agricultural productivity, enhancing the adoption of climate resilience, and mitigating greenhouse gas emissions.